2015
DOI: 10.3390/w7062707
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Disaggregation of Areal Rainfall Using Two Different Artificial Neural Networks Models

Abstract: Abstract:The objective of this study is to develop artificial neural network (ANN) models, including multilayer perceptron (MLP) and Kohonen self-organizing feature map (KSOFM), for spatial disaggregation of areal rainfall in the Wi-stream catchment, an International Hydrological Program (IHP) representative catchment, in South Korea. A three-layer MLP model, using three training algorithms, was used to estimate areal rainfall. The Levenberg-Marquardt training algorithm was found to be more sensitive to the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Different statistical and data-driven models have been used for temporal disaggregation of rainfall. A number of recent studies reported promising performance of ANN in temporal disaggregation of rainfall [41][42][43][44][45][46][47]. Zhang et al [43] used ANN for disaggregation of rainfall for West-Central Florida, and reported that the disaggregation of rainfall using ANN is promising.…”
Section: Disaggregation Of Daily Rainfall and Generation Of Projectedmentioning
confidence: 99%
“…Different statistical and data-driven models have been used for temporal disaggregation of rainfall. A number of recent studies reported promising performance of ANN in temporal disaggregation of rainfall [41][42][43][44][45][46][47]. Zhang et al [43] used ANN for disaggregation of rainfall for West-Central Florida, and reported that the disaggregation of rainfall using ANN is promising.…”
Section: Disaggregation Of Daily Rainfall and Generation Of Projectedmentioning
confidence: 99%
“…An ANN is a parallel information processing system with a set of neurons arranged in one or more hidden layers [53]. The MLP, which is an explicit form of the ANNs model, consists of three (or more) layers with an input layer (where the data are fed into the model), one (or more) hidden layer (where the data are processed to construct a model), and an output layer (where the results are generated) [54][55][56][57]. The neurons are connected by appropriate weights in each layer to the neurons in continuous layers.…”
Section: Multilayer Perceptron (Mlp) Neural Network Modelmentioning
confidence: 99%
“…The paper by Kim and Singh [23] entitled Spatial Disaggregation of Areal Rainfall Using Two Different Artificial Neural Networks Models presents the development of two artificial neural network models, namely, the multilayer perceptron and Kohonen self-organizing feature map, for spatial disaggregation of areal precipitation in the Wi-stream catchment in South Korea. For the three-layer multilayer perceptron model, three training algorithms, namely, Levenberg-Marquardt, conjugate gradient and quickprop, are employed to compute areal precipitation.…”
Section: Contributorsmentioning
confidence: 99%